(untitled) (World Bulletin of Social Sciences, 2021)
This article is about the culture of the speech, elocution and the history of the speech, communicative aspects of the speech, speech etiquette and standards of literary language. Besides, in this article is spoken about important aspects of well-bred speech formulation in professional human activity